Value creation and sorghum-based products: what synergetic actions are needed? - Yared Deribe; Etaferahu Kassa (Cogent Food & Agriculture, 2020)
Sorghum is a crop of marginal and vulnerable areas that are highly susceptible to the changing climate. A firm-level survey was conducted to address the level of utilization of the sorghum grain, associated value creation and constraints in the agro-processing segment of the agrifood value chain. Results declare that wheat is the most popular and commercial crop that has been widely utilized for the manufacturing of different food products. Maize is the second potential grain while the large share more allocates to the manufacturing of feed and fortified food products. The grains of teff, rice, and sorghum are majorly restricted to traditional food products. To a very limited extent, the agro-processing utilization of sorghum is more attributed to the manufacturing of baby foods and feed products. The physical features and nutritional qualities of sorghum products, experience and awareness gaps, and consumer perceptions remain to be the major barriers that limit the competitiveness of sorghum. The complex nature of the system demands empirical research, agribusinesses, and development actors to join hands embarking on the enhancement of nutrition, capacity development, product innovations, and demand creation. Moreover, boosting up of farm productivity, promoting farmer-industry partnerships and backups to the infant agro-processing sector opens up the opportunities for the disconnected sorghum growers.